Staphylococcus aureus controls eicosanoid and specialized pro‐resolving mediator production via lipoteichoic acid. Issue 1 (9th March 2022) - Miek, Laura; Jordan, Paul M.; Günther, Kerstin; Pace, Simona; Beyer, Timo; Kowalak, David; Hoerr, Verena; Löffler, Bettina; Tuchscherr, Lorena; Serhan, Charles N.; Gerstmeier, Jana; Werz, Oliver
Abstract: Staphylococcus aureus causes severe infections associated with inflammation, such as sepsis or osteomyelitis. Inflammatory processes are regulated by distinct lipid mediators (LMs) but how their biosynthetic pathways are orchestrated in S . aureus infections is elusive. We show that S . aureus strikingly not only modulates pro‐inflammatory, but also inflammation‐resolving LM pathways in murine osteomyelitis and osteoclasts as well as in human monocyte‐derived macrophages (MDMs) with different phenotype. Targeted LM metabololipidomics using ultra‐performance liquid chromatography‐tandem mass spectrometry revealed massive generation of LM with distinct LM signature profiles in acute and chronic phases of S . aureus ‐induced murine osteomyelitis in vivo. In human MDM, S . aureus elevated cyclooxygenase‐2 (COX‐2) and microsomal prostaglandin E2 synthase‐1 (mPGES‐1), but impaired the levels of 15‐lipoxygenase‐1 (15‐LOX‐1), with respective changes in LM signature profiles initiated by these enzymes, that is, elevated PGE2 and impaired specialized pro‐resolving mediators, along with reduced M2‐like phenotypic macrophage markers. The cell wall component, lipoteichoic acid (LTA), mimicked the impact of S . aureus elevating COX‐2/mPGES‐1 expression via NF‐κB and p38 MAPK signalling in MDM, while the impairment of 15‐LOX‐1 correlates with reduced expression of Lamtor1. In conclusion, S . aureus dictates LM pathways via LTA resulting in a shift from anti‐inflammatory M2‐like towards pro‐inflammatory M1‐like LM signature profiles. Abstract : Here we show that Staphylococcus aureus ‐induced murine osteomyelitis is associated with distinct lipid mediator signature profiles in acute and chronic phases. Experiments on the cellular level with human monocyte‐derived macrophages reveal that S . aureus modulates the expression of lipid mediator pathways towards a pro‐inflammatory pattern, seemingly mediated by lipoteichoic acid. These results help to explain how S . aureus infections mediate the inflammatory reactions associated with infectious diseases and will be of relevance for pharmacological interventions with S . aureus infections by adjusting favourable lipid mediator profiles.